Application of TPACK for Student Learning Motivation in Science Subjects in Elementary School - Herwanto, Agus; Wati, Unik Ambar; Senen, Anwar; Nurhayati, Nurhayati; Marwan, Marwan (Mimbar Sekolah Dasar, 2024)
Motivation Learning science and technology in elementary school is a problem faced by teachers. Students think social studies lessons are boring so teachers need to apply Technology Pedagogy and Content Knowledge (TPACK) to increase student learning motivation by integrating technology in learning, creating relevant, active and varied learning experiences, as well as facilitating effective collaboration between students, and can improve student engagement and understanding. This research aims to develop TPACK-based teaching media to increase learning motivation in Natural and Social Sciences (IPAS) learning. This research is included in the Research and Development (RD) category, using the ADDIE development model as stages in developing learning materials. Data collection techniques using interviews, observation, questionnaires and documentation. Data analysis used parametric statistical methods, namely the t-test with a significance level of 0.05. The research results show that: (1) there are significant differences in motivation to learn science S especially historical material between the TPACK learning model and the conventional model, the t - test results show a significance value of 0.002 or sig (2-tailed) 0.05; (2) the use of the TPACK learning model has been proven to be more successful in increasing students' motivation in studying historical material compared to conventional approaches. This was revealed from the posttest results, where the experimental group that took part in TPACK-based learning achieved an average score of 71.52, while the conventional group only achieved an average score of 58.89.